2015
DOI: 10.2335/scs.43.352
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Analysis of Pseudoaneurysms in the Anterior Circulation Presenting with Subarachnoid Hemorrhage: Internal Carotid Anterior Wall Versus Other Artery Pseudoaneurysms

Abstract: Subarachnoid hemorrhage (SAH) occurs when a pre-existing aneurysm ruptures. Dissecting aneurysms may cause both SAH and pseudoaneurysm formation. We reviewed the records of 11 patients with pseudoaneurysms treated at our institute during the last 5 years. Six of the 11 patients had pseudoaneurysms at the anterior wall of the internal carotid (IC) artery, so-called blister-like aneurysms, while the other five patients had pseudoaneurysms at the posterior communicating artery or anterior cerebral artery. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Nonbranching aneurysms have been pathologically reported to be caused by pseudoaneurysms resulting from a small disruption of the internal elastic lamina. It has also been reported that half of the pseudoaneurysms formed in the main artery for anterior circulation other than the ICA that were found to be the cause of SAH had lacerations in the vessels that were considered normal on imaging, indicating that the aneurysm itself was formed by a thrombus [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonbranching aneurysms have been pathologically reported to be caused by pseudoaneurysms resulting from a small disruption of the internal elastic lamina. It has also been reported that half of the pseudoaneurysms formed in the main artery for anterior circulation other than the ICA that were found to be the cause of SAH had lacerations in the vessels that were considered normal on imaging, indicating that the aneurysm itself was formed by a thrombus [1].…”
Section: Discussionmentioning
confidence: 99%
“…In our case, trapping with high-flow bypass was the safest and most reliable treatment procedure for a pseudoaneurysm in a non-branching M1 segment. In general, pseudoaneurysms require a more careful treatment method because they have walls formed by very fragile thrombi and bleed easily [1]. To date, an effective treatment approach for pseudoaneurysms has not been determined, and trapping with bypass has been considered the standard technique for an aneurysm of the anterior wall of the ICA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood blister aneurysms (BBAs) in the internal carotid artery (ICA) are relatively rare (0.5%-2.0% of all ICA aneurysms) and commonly located on the non-branching site (i.e., anterior wall of the ICA); however, recent reports showed that they also occurred in other arteries. [1][2][3][4][5] BBAs are characterized by small size (<3 mm), lack of an identifiable neck, thin and fragile wall, and rapid growth, being prone to rebleeding. [6][7][8][9][10][11][12][13][14][15] Although those larger than 3 mm are not technically called BBAs, previous reports indicated that some BBAs exhibited rapid morphological changes and progressed to saccular appearances with the formation of pseudoaneurysms (PAs).…”
Section: Introductionmentioning
confidence: 99%